ICON REPRESENTATION IN 'OZYMANDIAS' AND 'THE NEW COLOSSUS' POETRY: SEMIOTICS ANALYSIS - Ingga Rosarini (Faculty of Cultures and Languages UIN Raden Mas Said, 2020)
Semiotic or semiology means the systematic study of signs. What becomes difficult is defining what a 'sign' actually is. Modern day Semioticians, not only study 'signs' - it goes much deeper than that - they study how meaning is formed. Semiotic study how people first of all interprate a sign, how they then draw on cultural or personal experience to understand a sign. Pierce distinguished sign into three basic, there are: iconic, indexical, and the symbolic. An Icon has a physical resemblance to the signified, the thing being represented. Ozymandias is a fourteen-line sonnet by Percy Bysshe Shelley as English Romantic poet published in 1818. Ozymandias is a statue for another name of King Ramses the Great, Pharaoh of the nineteenth dynasty of ancient Egypt. The icon is depicted directly in the poem which represents the figure of king Ramses II with a statue. The new colossus is a statue for a classic American poem have fourteen-line sonnet by Emma Lazarus. The New Colossus was written in 1883 which adorns the pedestal of the statue of Liberty. The depiction of the character 'Mother of Exiles' as evidenced by the Statue of Liberty woman was written with the truth about what appeared and was seen and a deep sense of freedom. The portrayal depicted in the poem is immediately explained in terms of the denotation in its basic and original form. The depiction of the king's character was written with the truth of what appeared and was seen.